PERAN DIPLOMASI POLITIK LUAR NEGERI DAN ANGKATAN PERANG DALAM MEWUJUDKAN STABILITAS NASIONAL - Widya Noventari (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2014)
In this dynamic era, national defense concept towards national stability becomes veryimportant study in the life of the nation. This study is then used to determine the purpose and strategy of a country, and the country’s position in the arena of international politics. In this case, Indonesia has the principle of independent and active foreign policy, in which Indonesia will no be interrupted by other countries. In this principle, the power of diplomacy take the role as the soft power. This soft power of course cannot be separated from the hard power, which are governmental power and military in strengthening national defense and maintaining national stability.